The role of UCP5 in cardiac aging and metabolism in Drosophila. - Zhang, Y.; Zhai, Y.; Bai, Y.; Zeng, Q.; Tang, M. (Biochimie, 2025)
Uncoupling proteins, as mitochondrial transporters, allow protons to enter the mitochondrial matrix without generating ATP, a process known as oxidative phosphorylation uncoupling. Mammalian UCPs have been demonstrated to regulate metabolism, modulate reactive oxygen species levels, and maintain calcium homeostasis, which is closely linked to cardiac disease. In Drosophila, four homologs of uncoupling protein have been identified, with only UCP5 being detected in the adult heart proteome by mass spectrometry. The essential role of Drosophila UCP5 in the heart remains unknown. Our results showed that cardiac-specific UCP5 overexpression increased the incidence of fibrillation in an age-dependent trend, while cardiac-specific UCP5 knockdown induced an age-dependent increase in the incidence of asystoles, likely due to tachycardia. Additionally, UCP5 RNA levels significantly decline with age, indicating a role of UCP5 in cardiac aging. Cardiac-specific UCP5 overexpression reduced the reactive oxygen species levels within the cardiomyocyte nuclei and extended the lifespan. UCP5 RNA levels increased under high-fat diet conditions, and systemic overexpression of UCP5 can lower triglyceride levels under such dietary conditions, indicating an adaptive role of UCP5 in metabolism.